Three types of Photosystem II photoinactivation : I. Damaging processes on the acceptor side - Setlík, I; Allakhverdiev, S I; Nedbal, L; Setlíková, E; Klimov, V V (Photosynthesis research, 1990)
Oxygen evolving photosystem II particles were exposed to 100 and 250 W m(-2) white light at 20°C under aerobic, anaerobic and strongly reducing (presence of dithionite) conditions. Three types of photoinactivation processes with different kinetics could be distinguished: (1) The fast process which occurs under strongly reducing (t 1/2≅1-3 min) and anaerobic conditions (t 1/2≅4-12 min). (2) The slow process (t 1/2≅15-40 min) and (3) the very slow process (t 1/2>100 min), both of which occur under all three sets of conditions.The fast process results in a parallel decline of variable fluorescence (F v) and of Hill reaction rate, accompanied by an antiparallel increase of constant fluorescence (F o). We assume that trapping of QA in a negatively charged stable state, (QA (-))stab, is responsible for the effects observed.The slow process is characterized by a decline of maximal fluorescence (F m). In presence of oxygen this decline is due to the well known disappearance of F v which proceeds in parallel with the inhibition of the Hill reaction; F o remains essentially constant. Under anaerobic and reducing conditions the decline of F m represents the disappearance of the increment in F o generated by the fast process. We assume that the slow process consists in neutralization of the negative charge in the domain of QA in a manner that renders QA non-functional. The charge separation in the RC is still possible, but energy of excitation becomes thermally dissipated.The very slow photoinactivation process is linked to loss of charge separation ability of the PS II RC and will be analyzed in a forthcoming paper.